Readings in evidence based social work : Syntheses of the intervention knowledge base - Michael G Vaughn; Howard, Mathew O; Thyer, Bruce A (New Delhi Sage, 2009)
Exposing readers to "what works" across a wide range of practice domains, Readings in Evidence-Based Social Work meets a growing need within schools of social work to incorporate the latest research on evidence-based practice into the curriculum. This one-of-a-kind reader synthesizes current knowledge, adds editorial commentary and questions, and presents state-of-the-art material to help students better understand which social work interventions work and why.
Keywords: Social Work